2006
DOI: 10.1111/j.0105-1873.2006.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory, clinical and physiological factors in sensitive skin: a review

Abstract: Certain individuals experience more intense and frequent adverse sensory effects than the normal population after topical use of personal care products, a phenomenon known in popular usage as sensitive skin. Consumer reports of sensitive skin are self-diagnosed and often not verifiable by objective signs of physical irritation. Companies who manufacture cosmetic and personal care products are challenged to provide safe products to an audience with tremendous differences in skin type, culture and habits. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
130
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 65 publications
0
130
0
1
Order By: Relevance
“…In general, the vulvar area is more hydrated, with a higher coefficient of friction than other skin [21,26]. For an extensive review of permeability in the vulva area, see a recent review by Farage et al [40].…”
Section: Hormonal Changes In Cutaneous Tissuesmentioning
confidence: 99%
“…In general, the vulvar area is more hydrated, with a higher coefficient of friction than other skin [21,26]. For an extensive review of permeability in the vulva area, see a recent review by Farage et al [40].…”
Section: Hormonal Changes In Cutaneous Tissuesmentioning
confidence: 99%
“…It should be noted as well, however, that previous studies, have not found significant racial differences in overall skin sensitivity [1,8]. Similar age-dependent disparities in skin structure and function exist, also with potential to affect skin sensitivity (i.e, barrier function, capacity for skin repair, innervation of the skin and nerve function) [29] so it is possible that the fact that the Mississippi population was statistically older than the Cincinnati population may have influenced results. In previous studies, however, no significant impact of age on skin sensitivity has been observed [1,12].…”
Section: Discussionmentioning
confidence: 86%
“…This disparity could have influenced the respective prevalence of sensitive skin in the two areas, as ethnic differences in skin structure and function with a potential to influence skin sensitivity have been observed, (e.g. thickness and lipid content of the stratum corneum, resistance of stratum corneum to stripping, and Number of subjects who responded to the questionnaire questions-n = number of subjects who with any level of perceived sensitivity; N = total responders c The chi-squared analysis was conducted to identify association between perceptions of sensitivity and the respective environmental factor d The phi coefficient tested the strength of the association; the higher the value, the closer the association with a perception of sensitive skin MS = De Soto County, Mississippi; n = number of subjects with very sensitive skin; OH = Cincinnati, Ohio; N = number of subjects with any skin sensitivity MS = De Soto County, Mississippi; n = number of subjects with sensitive skin; OH = Cincinnati, Ohio; N = number of subjects with any skin sensitivity a Slightly, moderately, or very sensitive skin [29]. In order to facilitate statistical comparison or the Mississippi and Ohio populations, therefore, the Hispanic and Asian subjects were eliminated from the Cincinnati cohort for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, children with atopic dermatitis had lower PPD induration size compared to healthy donors, but this was not statistically significant (Gruber, et al, 2001, Yilmaz, et al, 2000. In humans, sensitive skin is defined as reduced tolerance to cutaneous stimulation, with symptoms ranging from visible signs of irritation to subjective neurosensory discomfort (Farage, et al, 2006, Willis, et al, 2001). The question of whether human AD patients are more prone to allergic contact dermatitis than nonatopic individuals is still controversial (Mailhol, et al, 2009).…”
Section: Altered Immunobiology Response In Flaky Tail Mousementioning
confidence: 98%
“…The skin abnormality associated with AD is well known to be a predisposing factor to sensitive skin (Farage, et al, 2006, Willis, et al, 2001) and allergic contact dermatitis (Clayton, et al, 2006, Mailhol, et al, 2009). However, children with atopic dermatitis had lower PPD induration size compared to healthy donors, but this was not statistically significant (Gruber, et al, 2001, Yilmaz, et al, 2000.…”
Section: Altered Immunobiology Response In Flaky Tail Mousementioning
confidence: 99%